A Dynamic Model of the Firm: Structural Explanations of Key Empirical Findings. Issue 3 (August 2015) - Lazzati, Natalia; Menichini, Amilcar A.
Abstract We derive a dynamic model of the firm in the spirit of the trade‐off theory of capital structure that explains firm behavior in terms of firm characteristics. We show our model is consistent with many important findings about the cross‐section of firms, including the negative relations between profitability and leverage, and between dividends and investment‐cash flow sensitivities. The model also explains the existence of zero‐debt firms and their observed characteristics. These results have been used to challenge the trade‐off theory and the assumption of perfect capital markets. We revisit these critiques and provide structural explanations for the regularities we replicate.